1972
DOI: 10.1515/zna-1972-0317
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of Dynamical Diffraction at a Bragg Angle of about π/2

Abstract: The diffraction phenomena of X-rays in the case ΘB≅π/2 are studied on the basis of dynamical theory. The angular width of diffraction for ΘB= π/2, 2√|χh| , is about 103 times as broad as the one for ΘB ⪡π/2, 2|Xh|/sin ΘB . Similar characteristic phenomena are expected for electrons. The π/2 Bragg angle diffraction would be utilized as X-ray resonator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
2

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 6 publications
1
28
2
Order By: Relevance
“…This was first treated by Kohra and Matsushita. 7 More recently, the application of Bragg backscattering to lattice constants measurements was discussed by Shvyd'ko et al 8 The experimental arrangement of the present experiment is shown in Fig. 1.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This was first treated by Kohra and Matsushita. 7 More recently, the application of Bragg backscattering to lattice constants measurements was discussed by Shvyd'ko et al 8 The experimental arrangement of the present experiment is shown in Fig. 1.…”
mentioning
confidence: 82%
“…Thwelis 3 found a difference in the lattice constants of 6 LiF and 7 LiF of the order of two parts in ten thousand. Buschert et al, 4 using an x-ray spectrometer which was designed and built for high-precision measurements of lattice parameters of perfect single crystals, determined the lattice parameter of an isotopically enriched ͑95.8%͒ sample of 74 Ge of high crystal perfection, and compared with natural Ge (M ϭ72.6).…”
mentioning
confidence: 99%
“…6 and 13 it was shown that an energy scanned XSW measurement at B ϭ/2 is much less sensitive to imperfections of the crystal because of a wide ͑of order 1°) Bragg reflection width. 14 Here it is shown that the energy dependence of the x-ray absorption at B ϭ/2 is also measured in polycrystalline samples. The elastic scattering is expected to produce a step structure at the same energy position because of appearance of a new Debye-Scherrer cone.…”
mentioning
confidence: 87%
“…The dynamical theory of diffraction predicts that at this angle the Darwin-Prins rocking curve has an extreme angular width, which typically exceeds the mosaic spread caused by strain in most metal crystals [21,22]. The coherence of the standing waves is thus maintained even in imperfect samples.…”
Section: (Received 28 August 1998)mentioning
confidence: 99%